CARIES PREVENTION THROUGH THE APPLICATION OF PIT AND FISSURE SEALANTS FOR MAKASSAR ELEMENTARY SCHOOL STUDENTS - Ira Liasari; Ardian Priyambodo; Munadirah Munadirah; Jumriani Jumriani; Nurhaeni Nurhaeni; Asriawal Asriawal (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Dental and oral diseases are progressive and accumulative diseases that can affect all age groups. Dental caries is the most common dental disease in Indonesia. One of the preventive measures is to apply pit and fissure sealants to teeth with deep pits and fissures. Objective: The purpose of this activity is to help improving the oral health of the community through preventive efforts in the form of pit and fissure sealant applications. Methods: The implementation of this community service activity was conducted through several stages, namely preparation, data collection, problem identification, and implementation of activities. Results: The average caries index of the targeted students was in the high category. There were 5 children who need pit and fissure sealant application. Conclusion: This community service activity had been conducted according to plan. The community, in this case elementary school students, got preventive services in the field of dental health, especially the application of pit and fissure sealants.